EARLY VASOSPASM FOLLOWING SPONTANEOUS SUBARACHNOID HEMORRHAGE: A CASE REPORT - Živković, Slavko; Ilić, Jovan; Nikolov, Vesna; Stokanović, Vesna; Mitić, Radisav; Todorović, Stefan; Djordjević, Marija (Acta medicae Medianae, 2022)
An ultraearly cerebral vasospasm (UEAV) occurs within 48 hours after aneurysm rupture, can be verified by angiographic imaging and usually has a poor outcome. The presented patient had clinical symptomatic UEAV, detected within a few hours of bleeding from the Anterior Communicating artery aneurysm. The neurosurgical team decided on late operation, more precisely 18 days after the rupture of the aneurysm, because the patient was then giving clinical signs of cerebral vasospasm relief. Right pterygoid craniotomy was performed. The aneurysm was excluded from circulation by clipping without any incident. When treating patients who have clinical signs of UEAV, the ruptured aneurysm site should be verified by angiographic imaging as soon as possible, while the appropriate treatment modality should be carefully and duly considered. Keywords: intracranial vasospasm, Anterior Communicating artery aneurysm, surgical clip
Keywords: intracranial vasospasm, anterior communicating artery aneurysm, surgical clip